Analysis of trapping parameters of KCaSO4Cl:Eu phosphor prepared by acid method - Kore, Bhushan; Dhoble, N S; Dhoble, S J (Recent Research in Science and Technology, 2012)
This paper reports the systematic study of KCaSO4Cl:Eu phosphor synthesised by acid distillation method. Single glow peak at 432 is observed in KCaSO4Cl:Eu phosphor. The study of trapping parameters is done with the help of Chen’s peak shape method.